Seni Cinta; Menggugat Maskulinitas Cinta - Nikodemus Niko (Sosial Budaya, 2018)
This article using perspective of sociology of love in described love and see how love are very resilient with the Indonesia culture of patriarchy, included the description of masculinity love. Love used as an anomaly that is absolutely. Even absolute backfire for mankind cult of love. Sociology of love is not lay away to love as selfish person, on the other hand the power of love which dispatch people to peace. The illustrations and examples in this paper is based on knowledge and personal experience of mine. This paper write done by digging of various sources reference, which is I speculate by inference Freud said that love in now is still in animality essence. The masculine love is still adhered to this esence, and still alives in Nusantara’s culture.